Determination of dose rate during the inspection of spent fuel element in the testing cell (Brazilian Journal of Radiation Sciences (BJRS), 2020)
Testing cell a hot cell is responsible for inspecting the spent fuel elements in open pool type reactor. Because the spent fuel elements examination in the testing cell would result in rising in radiation dose level, a previous precaution should be estimated to ensuring the radiation protection safety and the prevention of radiation hazard for the workers during the process. The most efficient precaution against these kinds of work is the estimation of the predicted radiation dose level around the hot cell during the inspection process. In this regard, a MCNP model was performed to simulate the spent fuel element inspection inside the hot cell to estimate the radiation dose level around the testing cell during the process. The dose rate, during the inspection of the spent fuel element, would be estimated at different decay times for different burn-up. The calculations show that the minimal decay times required to manipulating the spent fuel element would range between 120 to 270 days for burn-up ranging between 18745 and 101224.4 MWD/TU.